Low-frequency fiber optic hydrophone based on ultra-weak fiber Bragg grating - Luo, Zhihui; Ding, Shuai; Tan, Chao; Xu, Bing; Lu, Bo; Huang, Jianglou (IEEE sensors journal, 2023)
A winding low-frequency hydrophone based on ultra-weak fiber Bragg grating was studied. Through analyzing the hydrophone principle and the sensitivity factors, such as the material, radius, and thickness of the elastic cylindrical shell, the probe structure was optimized. In addition, an adaptive filtering technique based on the least mean square algorithm was introduced to improve the signal-to-noise ratio of the system. A low-frequency hydrophone with a working depth of 100 m and a diameter of 15 mm was developed and validated using the moving-water-column method. Results showed that the average acoustic pressure sensitivity of the hydrophone in the range of 1-100 Hz was -144.836 dB (re rad/μPa), the acoustic pressure sensitivity at 1 Hz was up to -130.85 (dB re rad/μPa). After using LMS filtering algorithm, the maximum signal-to-noise ratio of hydrophone can be increased by 4.62 dB, and the minimum detection pressure is 1.69×10 -4 Pa/Hz 1/2 . This hydrophone with high sensitivity and signal-to-noise ratio provides a reference for low-frequency underwater detection.